On the Knowledge of University Students About the Strategies of National Sustainable Development - Gáthy, Andrea (Acta Agraria Debreceniensis, 2004)
The definition of sustainable development has a past which spans two decades. Today it is evident that the three pillars of sustainable development – environment, economy and society – have a strong correspondence and equally effect on every people. The UN’s Environment and Development Conference in 1992 declared the requirement in the document of Objectives for the XXI. century, that governments should prepare national sustainable development strategies. The World Conference of Sustainable Development in August 2002 made a stronger decision: „the states should make immediate steps forward … defining and preparing their national sustainable development, and for the purpose to start its realization until 2005”. Most of the countries fulfilled these requirements, and the Hungarian government promises to prepare its national strategy by the end of 2004. The aim of my study is to survey the knowledge of university students about the above mentioned process and generally about the topic of sustainable development. The selection of the target group is justified by the importance of young intelligentsia in the future. In order to examine their knowledge, I prepared a questionnaire and from the emerging primary data, my conclusion and statements have been deducted by a processing-analysing course, on the bases of which I made my suggestions.